If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 12 = 3b + 8 Reorder the terms: 12 + 2b = 3b + 8 Reorder the terms: 12 + 2b = 8 + 3b Solving 12 + 2b = 8 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 12 + 2b + -3b = 8 + 3b + -3b Combine like terms: 2b + -3b = -1b 12 + -1b = 8 + 3b + -3b Combine like terms: 3b + -3b = 0 12 + -1b = 8 + 0 12 + -1b = 8 Add '-12' to each side of the equation. 12 + -12 + -1b = 8 + -12 Combine like terms: 12 + -12 = 0 0 + -1b = 8 + -12 -1b = 8 + -12 Combine like terms: 8 + -12 = -4 -1b = -4 Divide each side by '-1'. b = 4 Simplifying b = 4
| logx(1/8)=3 | | Xsquared-3x-28=0 | | -2(x+5)-7=-x+13-5x | | 20y+6=14 | | x^5-5x^3+2-2x^3= | | 4x-3=7x+4 | | 4(a+6)=4 | | 100x+100y+65z= | | 9(2x-1)-20+4x=20(3x-5)-5 | | 10x+7=7(x+2)-1 | | 100x+100y+656z= | | 64/100 | | 5a^2+a^3-3a^2+a= | | 3(x+7)=5x+21 | | 5a=3a-8 | | 2x-6+3(x+5)=3x+x+1 | | 54-11x=108-2x | | 5x+15over(x-9)(x+9)= | | 2+3x^2+x^4-3x^2+1= | | 5(x+9)=69 | | y=3x^3-3x^2-3x-1 | | 5d(3-d)+d(2d-1)= | | x+(2x)+(2+6x)=38 | | 4e^2x=4 | | 2x+(2x-4)=0 | | 3/8(5x-3)=0 | | 3(x-2)=11+2(x+1) | | 8x+1=-5-x | | E=Q-t1/t2 | | 2y-4x(2x+1)=2 | | 8x+1=-5-1x | | x^2-5x+4-x^2+6x-3= |